Energy auditing in Kolej Mawar, Universiti Teknologi MARA Shah Alam: article / Mohamad Suid Ismail - Ismail, Mohamad Suid (2009)
The global warming arouse the awareness of the public in the energy saving. New energy saving technology is appearing and developing rapidly, at the same time energy regeneration or alternative technology are developing in large scale. Basically energy problem can be classified into the following solution in general: energy saving, energy searching and energy recycling. Energy saving is defined as the differences between actual energy intensity and anticipated intensity. This project presents the system equipment efficiency at Kolej Mawar, Univesiti Teknologi Mara Shah Alam using Matrix Energy Saving (MES-30) equipment with autotransformer. The energy usage is determined from the historical data and walkthrough audit. Opportunity for improving the energy consumption were identified and evaluated. The economic analysis was carried out to determine the payback period.